Generalized Pruritus and Gradual Loss of Vision as the Presenting Complaints of Acute HIV Infection: Management Challenges during COVID-19 Pandemic - Shrebash Paul; S. M. Mahbubur Rahman; Rajibur Rahman; Mahbubur Rahman; Quazi Mamtaz Uddin Ahmed; Rafiqul Alam; Fazle Rabbi Chowdhury (Case Reports in Infectious Diseases)
Background. Although the prevalence of HIV is low in Bangladesh, there is a potential for an increased number of cases. This is because of high cross-border mobility (India and Myanmar) of people and increased injection drug abusers amongst youth in the cities and rural areas, HIV can present in many ways, from asymptomatic to advanced disease, including various atypical (generalized itching) and advanced (loss of vision) manifestations. A high degree of suspicion is required to diagnose HIV in a country like Bangladesh. Early diagnosis and prompt treatment are essential to have a better outcome. Methods. Here, we report two thought-provoking cases where patients were suffering from generalized itchy lesions (pruritic papular eruption) throughout the body for a long time and gradual loss of vision in another case. Results. Due to lack of suspicion, initially, HIV screening was not done. Both patients visited several health centres, but no diagnosis was made. Moreover, COVID-19 pandemic worsens the situation. Finally, they were diagnosed with HIV; unfortunately, one of them lost her vision due to CMV retinitis and another patient died of other complications. Conclusion. Ongoing COVID-19 pandemic put many challenges to ensure optimum care, especially for patients with long-sufferings like HIV. Clinicians have to have a very high degree of suspicion while dealing with patients presented with rare manifestations, particularly in a low endemic clinical setting.